ASSESSMENT FOR PROGRAMMING SUBJECT IN HIGHER EDUCATION: A STRUCTURED REVIEW - Ismail, Nor Zalina; Razak, Mohd Rizal; Kadir, Khairunnisa A.; Abdul Rahman, Rozeleenda; Zainal, Mohd Azim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
Assessment is quite important for making higher education programming courses effective for both teachers and students. Programming is still a basic skill in computer science and related professions; thus, it’s very important to come up with and use the right ways to test students to make sure they do well and that the school is honest. Even though there is more and more research on the subject, we still need to carefully look at how programming tests are set up, graded, and improved using new ideas. The title of this structured systematic literature review (SLR) is "Assessment for Higher Education in Programming Subject: A Structured Review." Its goal is to bring together existing research on how programming education is assessed. Following the PRISMA process, the review was done to make sure it was open and followed strict rules. After a systematic procedure of finding, screening, assessing eligibility, and inclusion, 34 primary studies were chosen from three major academic databases: Web of Science, Scopus, and ERIC. We grouped the findings from the chosen literature into three main areas: (1) Programming Assessment and Evaluation Strategies, which looks at the design, effectiveness, and difficulties of formative and summative assessment models; (2) Innovative Approaches in Programming Education, which focusses on how automation, gamification, and adaptive technologies can be used in assessment design; and (3) Academic Integrity and Student Performance in Programming, which talks about worries about cheating, test anxiety, and fairness in digital assessment settings. The review shows that even if many new and data-driven ways of testing have made students more interested and enhanced their learning, problems like inconsistent feedback, anxiety during automated testing, and cheating still exist. This study adds to the body of knowledge by showing what makes a good assessment framework and pointing out areas where more research is needed in programming education.